2004
DOI: 10.1002/we.120
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic stability predictions for a MW‐sized blade

Abstract: Classical aeroelastic flutter instability historically has not been a driving issue in wind turbine design. In fact, rarely has this issue even been addressed in the past. Commensurately, among the wind turbines that have been built, rarely has classical flutter ever been observed. However, with the advent of larger turbines fitted with relatively softer blades, classical flutter may become a more important design consideration. In addition, innovative blade designs involving the use of aeroelastic tailoring, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 6 publications
1
50
1
Order By: Relevance
“…(12). The resulting curve ( △ line) largely underestimates the section utter limit for most of the frequency ratios, as also observed on a rigid airfoil by Hansen [18] and on a full blade by Lobitz [17]. It is therefore concluded that the wake vorticity has a stabilizing e ect that can not be neglected in a stability analysis.…”
Section: Unde Ected Elastic Flapmentioning
confidence: 61%
See 1 more Smart Citation
“…(12). The resulting curve ( △ line) largely underestimates the section utter limit for most of the frequency ratios, as also observed on a rigid airfoil by Hansen [18] and on a full blade by Lobitz [17]. It is therefore concluded that the wake vorticity has a stabilizing e ect that can not be neglected in a stability analysis.…”
Section: Unde Ected Elastic Flapmentioning
confidence: 61%
“…In Theodorsen and Garrick's formulation, the e ects on the aerodynamic forces from the vorticity shed into the wake are modeled by complex Bessel functions that depend on the utter frequency itself, therefore a recursive solution is required to determine the stability limit. A similar formulation is adopted by Lobitz [17], who modi es the model to determine the utter limits of an isolated wind turbine blade rotating in still air. Lobitz concludes that, for a 1.5 MW wind turbine blade, utter would occur if the rotor over-speeds up to double the nominal rotational speed.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed for fatigue and ultimate loads, neglecting the circulatory lift dynamics in attached flow causes the largest variations in the simulated response. The stability limit encountered with the quasi-steady assumption is in fact much lower than in the other two cases; Lobitz [29] reported a similar result for the flutter limit of an isolated blade. The finite-thickness indicial lift response function results in slightly higher stability limits, but the difference from the flat plate case is rather small; variations of similar magnitude were reported in the flutter analysis of a 2D profile [30].…”
Section: Stability Limitsmentioning
confidence: 69%
“…Flap-twist to feather coupling reduces damping while damping increases for flaptwist to stall coupling. Lobitz (2004) investigates the flutter speed of an uncoupled and a bend-twist to feather coupled megawatt-sized wind turbine blade with quasi-steady and unsteady aerodynamic models, applying the Theodorsen's approach. Lobitz shows that quasi-steady flutter speeds are significantly lower than the flutter speeds obtained with unsteady aerodynamics.…”
Section: A R Stäblein Et Al: Modal Properties and Stability Of Benmentioning
confidence: 99%